2021
DOI: 10.1093/plphys/kiab531
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of CHH methylation through RNA-directed DNA methylation ensures sexual reproduction in rice

Abstract: DNA methylation is an important epigenetic mark that regulates the expression of genes and transposons. RNA-directed DNA methylation (RdDM) is the main molecular pathway responsible for de novo DNA methylation in plants. Although the mechanism of RdDM has been well studied in Arabidopsis (Arabidopsis thaliana), most mutations in RdDM genes cause no remarkable developmental defects in Arabidopsis. Here, we isolated and cloned Five Elements Mountain 1 (FEM1), which encodes RNA-dependent RNA polymerase 2 (OsRDR2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 101 publications
2
29
0
Order By: Relevance
“…Because Pol IV- and RDR2-generated siRNAs are the hallmarks of RdDM [ 4 , 15 ], we assessed CHH methylation on siRNA clusters. On both bill-siRNA and pau-siRNA clusters, the CHH methylation levels were significantly higher in inflorescences than in seedlings ( Figure 3 B), which is consistent with our previous finding that CHH methylation is globally higher in reproductive organs than in seedlings [ 11 ]. The CHH methylation on bill-siRNA and pau-siRNA clusters is significantly lower in osrdr2 inflorescences than in wild-type (WT; Nipponbare) inflorescences ( Figure 3 B), demonstrating that OsRDR2 -dependent bill-siRNAs as well as OsRDR2 -dependent pau-siRNAs are required for DNA methylation in inflorescences.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Because Pol IV- and RDR2-generated siRNAs are the hallmarks of RdDM [ 4 , 15 ], we assessed CHH methylation on siRNA clusters. On both bill-siRNA and pau-siRNA clusters, the CHH methylation levels were significantly higher in inflorescences than in seedlings ( Figure 3 B), which is consistent with our previous finding that CHH methylation is globally higher in reproductive organs than in seedlings [ 11 ]. The CHH methylation on bill-siRNA and pau-siRNA clusters is significantly lower in osrdr2 inflorescences than in wild-type (WT; Nipponbare) inflorescences ( Figure 3 B), demonstrating that OsRDR2 -dependent bill-siRNAs as well as OsRDR2 -dependent pau-siRNAs are required for DNA methylation in inflorescences.…”
Section: Resultssupporting
confidence: 91%
“…In a previous study, we found that the whole-genome methylation level (WGML) in the CHH context was higher in inflorescences than in seedlings mainly because of the up-regulation of RdDM machinery [ 11 ]. However, 24 nt siRNA abundance on the hyper-methylated differentially methylated regions (hyper-DMRs) of inflorescence relative to seedlings was significantly lower in inflorescences than in seedlings ( Figure S1A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ago4ab and rdr2 RNAi lines also showed reduced height and panicle size, and the ago4ab line phenocopied dcl3 in the flag leaf angle (Wei et al., 2014). Mutation in rice RDR2 showed defects in pollen grain development (L. Wang et al., 2022), while drm2 mutants showed a wide range of developmental phenotypes including complete sterility (Moritoh et al., 2012).…”
Section: Introductionmentioning
confidence: 99%